Antagonism of the acute hemodynamic effects of captopril in decompensated congestive heart failure by aspirin administration - Viecili,P.R. (2003)
The concomitant use of angiotensin-converting enzyme inhibitors and aspirin may cause pharmacological antagonism. Hence we examined the effect of aspirin on the neurohormonal function and hemodynamic response to captopril in heart failure patients. Between April 1999 and August 2000, 40 patients were randomized into four equal groups: 1) captopril, 2) aspirin, 3) captopril-aspirin: captopril was given alone on the first day, followed by aspirin on the remaining days, and 4) aspirin-captopril: aspirin was given alone on the first day, followed by captopril on the remaining days. Hemodynamic, norepinephrine and prostaglandin measurements were performed pre- and post-medication for 4 days. Captopril (50 mg) was given orally every 8 h and 300 mg aspirin was given on the first day, and 100 mg/day thereafter. In the captopril group and only on the first day of captopril-aspirin, captopril produced increases in cardiac index (2.1 ± 0.6 to 2.5 ± 0.5 l min-1 m-2, P<0.0001), and reduced peripheral vascular resistance (1980 ± 580 to 1545 ± 506 dyn s-1 cm-5/m², P<0.0001) and pulmonary wedge pressure (20 ± 4 to 15 ± 4 mmHg, P<0.0001). In contrast, aspirin alone or associated with captopril showed no significant hemodynamic changes. Norepinephrine decreased (P<0.02) only in the captopril group. Prostaglandin levels did not differ significantly among groups. Thus, aspirin compromises the short-term hemodynamic and neurohormonal effects of captopril in patients with acute decompensated heart failure.